EVALUASI JEMBATAN DAN SABO YANG DIFUNGSIKAN SEBAGAI JEMBATAN DI SUNGAI BOYONG YOGYAKARTA PASCA ERUPSI GUNUNG MERAPI 2010 - , Mega Ayundya Widiastuti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mount Merapi is one of 129 active volcanoes in Indonesia, which includes frequently erupt. On October 26, 2010 eruption of Mount Merapi have returned. This was the biggest disaster in comparison to similar disasters in the five previous time period ie 1994, 1997, 1998, 2001 and 2006. The continuing impact of the eruption of Mount Merapi, debris flow, potentially damaging the buildings contained in the rivers that disgorge at Mount Merapi, such as bridge including sabo dam functioned as a bridge. It is therefore important to evaluate condition of existing bridges and sabo post-eruption of Mount Merapi. The limited funds provided by the Government in an effort to restore function and condition of the bridge in one groove is the cause of the need for preparation of the scale of priorities, in order to determine the bridge that must be repaired first. The research begins with the collection of primary and secondary data, then the data were analyzed by assessing the condition of the damage that occurs in the elements of bridge and oprit. Bridge condition assessment refers to the Bridge Management System standard, while for oprit refer to the draft Urgent Disaster Reduction Project for Mt. Merapi Operation and Maintenance for Facilities Sabo. Further evaluation andformulation of priorities and recommendations handling of the bridge and sabo dam The impact of Mt. Merapi eruption in 2010 to the bridge and sabo which is functioned as a bridge on the River Boyong are increases in riverbeds and damage to the retaining wall on the bridge, ie Ngentak, Plemburan, Boyong, and Gemawang bridge,while the sabo is abrasion on the surface layers of all sabo which is functioned as a bridge and buried several components downstream of main dam, ie the BO-C8A, BO-C11B, BO-C4A. In terms of structures stability, the entire bridge is located on the river Boyong still safe to pass, except Wonosobo bridge and Kemiri bridge. Priorities for the handling of the bridge is divided into classes bridges, respectively ie class A (on the national road), class B bridge (on the district / city road), class C (on rural roads). Priority handling of class A are Tungkak, Boyong, Sudirman, Code Bridge